Почин української фольклористичної енциклопедії - Сокіл, В. (Народознавчі зошити, 2014)
Йдеться про створення повноцінної фольклористичної енциклопедії України. Коротко подається історіографія проблеми. Мета запропонованої роботи — узагальнення й
підсумки досвіду в ділянці української фольклористики.
Енциклопедія міститиме статті про персоналії, фольклорні
зібрання, часописи, у яких представлені народнопоетичні
матеріали, а також архівні джерела, профільні інституції,
установи, заклади тощо. Належне місце займуть фольклорні персонажі, як і жанри, теорія, поетика фольклору.
Пропонується читачам лише дещиця із великої теми, керівником якої є автор. In the article has been considered quite a wide field of problems
as for compilation of full-valued Ukrainian folkloristic encyclopedia.
A historyography of main tasks is to be exposed in short
review. Aims of the proposed work consist in generalization of
experience and in its summing up with dominant idea to be
used for development of Ukraainian folklore studies. The encyclopedia
is to enclose notes on personal data, folklore collections,
publications of people’s poetical materials as well as archive
sources, profiled instructions, institutions, establishments
etc. Proper places are to be spared for folklore personages and
for themes of genres, theories, folklore poetics. Small part of
texts belonging to the greater themamatic integrity, administered
by the author is now being presented to the audience. Речь идет о создании полноценной фольклхористической
энциклопедии Украины. Кратко излагается историография
проблемы. Цель предлагаемой работы — обобщение и итоги опыта в области украинской фольклористики. Энциклопедия будет содержать статьи о персональных даных, фольклорных собраниях, публикациях народнопоэтических материалов, а также архивных источниках, профильных
учреждениях, заведениях, организациях и т. п. Соответствующее место предназначено фольклорным персонажам,
как и жанрам, теории, поэтике фольклора. Вниманию читателей предлагается лишь незначительная часть материалов
большой темы, руководителем которой является автор.